2015
DOI: 10.1007/s00277-015-2482-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of GSTM1 and GSTT1 deletion polymorphisms with Pakistani aplastic anemia patients and controls and meta-analysis

Abstract: Interaction of environmental and genetic elements plays a vital role in the pathogenesis of aplastic anemia (AA). Glutathione S-transferase (GST) is a key detoxifying enzyme. Absence or low levels of this enzyme may genetically predispose individuals to AA. GST genes GSTM1 and GSTT1 are polymorphic. The aim of this study was to screen Pakistani AA patients and controls for GSTM1 deletion GSTM0 and GSTT1 deletion GSTT0 and perform meta-analysis using our data and other published data regarding these polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In the present study, we evaluated the association of GSTT1 genotypes with breast cancer-related parameters. We report a GSTT1 -absent frequency of 11% in the controls, which is in agreement with couple of earlier studies published from the region, one from Islamabad [33], and the other from Karachi [18]. In this study, we report a significant association of GSTT1 -absent genotype with increased breast cancer risk in a representative sample from Pakistani population.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we evaluated the association of GSTT1 genotypes with breast cancer-related parameters. We report a GSTT1 -absent frequency of 11% in the controls, which is in agreement with couple of earlier studies published from the region, one from Islamabad [33], and the other from Karachi [18]. In this study, we report a significant association of GSTT1 -absent genotype with increased breast cancer risk in a representative sample from Pakistani population.…”
Section: Discussionsupporting
confidence: 92%
“…Most data regarding the epidemiology of AA is derived from western literature [6][7][8][9][10] with only few published studies from the developing world [2,[11][12][13][14][15][16]. As noted above, marked geographic variation exist with higher prevalence in Asia [2,11] and Africa [3] as compared to Europe and the United States (US) [2,17].…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…Other smaller studies on some of these patients have revealed genetic predispositions for AA in FAS/FASL system, GSTM1 and GSTT1 and different HLA alleles [32][33][34]. Similarly, low fraction of PNH positivity may also point toward underlying non-immune mechanisms in the disease pathogenesis.…”
Section: Consanguinity and Genetic Factorsmentioning
confidence: 88%